Age‐ and sex‐specific reference intervals for superoxide dismutase enzyme and several minerals in a healthy adult cohort. Issue 9 (17th July 2021) - Ghazizadeh, Hamideh; Kathryn Bohn, Mary; Yaghooti‐Khorasani, Mahdiyeh; Kamel Khodabandeh, Atieh; Zare‐Feyzabadi, Reza; Timar, Ameneh; Mohammadi‐Bajgiran, Maryam; Oladi, Mohammad Reza; Rohban, Mohadeseh; Esmaily, Habibollah; Ferns, Gordon A.; Adeli, Khosrow; et al.
Abstract: Introduction: The aim of this study was to establish RIs for clinically important markers including superoxide dismutase (SOD), serum copper, zinc, calcium, magnesium, and phosphate in a cohort of healthy Iranian adults. Materials: A subsample from MASHAD cohort study was used to assess serum SOD, copper, zinc, calcium, magnesium and phosphate. Serum SOD was measured according to its inhibitory potential of pyrogallol oxidation. Micro‐ and macro‐minerals were measured using flame atomic absorption spectrometry and a BT3000 autoanalyzer, respectively. Sex‐ and age‐specific RIs were then calculated based on CLSI Ep28‐A3 guidelines. Results: Reference value distributions for studied parameters did not demonstrate any age‐specific differences that were statistically significant. In addition, sex partitioning was not required for all parameters, apart from serum magnesium, which showed a wider range in females (0.81–1.26 mg/dl) compared with males (0.82–1.23 mg/dl). Conclusion: The RIs established in this study can be expected to improve mineral assessment and clinical decision‐making in the Iranian adult population. Abstract : The aim of this study was to establish RIs for clinically important markers including superoxide dismutase (SOD) and serum copper, zinc, calcium, magnesium and phosphate in a cohort of healthy Iranian adults. Sex‐ and age‐specific RIs were then calculated based on CLSI Ep28‐A3 guidelines. Age and sex partitioning were not required for all parameters, apart from serum magnesium, which showed a wider range in females (0.81–1.26 mg/dl) compared to males (0.82–1.23 mg/dl).